Ring formation and hydration effects in electron attachment to misonidazole - Ončák, Milan (2019)
This research was funded by CZECH SCIENCE FOUNDATION grant number 19-01159S; Czech Ministry of Education Youth and Sports via OP RDE Grant no. CZ.02.2.69/0.0/16_027/0008355; S.D. acknowledges funding from the FWF, Vienna (P30332).